Perspektif Tubuh Menurut Teologi Tubuh dalam Maraknya Bentuk Perilaku Pornografi Melalui Media Sosial Pada Remaja - Martina Minaratih; Intansakti Pius X (Jurnal Magistra, 2023)
The Theology of the Body is a collection of Pope John Paul II's faith teachings or catechesis for pilgrims in St. Paul's Square. Peter every Wednesday between 5 September 1979 and 28 November 1984 during his pontificate. Theology of the Body gives birth to a reflection of faith about the meaning of human sexuality. The presentation of teachings in Theology of the Body aims to invite believers to respond to various deviant behaviors and ideas regarding the general human understanding of the body from the perspective of faith. The nature of the body is often assumed incorrectly. The body is seen as an object of sexual satisfaction and contains elements of a commodity in the economy. Another deviant perception of the body is only part of sexual gratification in today's era, marked by the widespread distribution of pornography via social media. Teenagers are the main target of today's concerns about the rapid spread of pornography via social media because today's teenagers are teenagers who are directly connected to internet-based social media in their daily lives. The internet is used as a medium for learning, work and even as a means of entertainment that offers instant features that make it easier for users to surf the virtual world. The purpose of writing this article is to describe Pope John Paul II's view of the body as a sacred gift that must be respected, the body as a means of God's direct relationship with His creation. Also describes four body characteristics that are very relevant to the current situation and describes teenagers' understanding of the body due to the rise in cases of spreading pornography via social media. This research uses a library study method by collecting data through journals, articles, books and other insights via the internet. Researchers read, redescribe and process the data so that it is relevant. The results of the research show that teenagers' dependence on social media is the main gateway to expanding the entry and distribution of pornography and becoming perpetrators of pornography. Teenagers need guidance from parents in their understanding of sexuality in using social media. The body perspective according to "Body Theology" can be a strong basis for minimizing the spread and behavior of pornography among teenagers